PENGARUH REPRESENTATIF, PEMASARAN DIGITAL MELALUI TRANSFORMASI INFORMASI DI BIDANG MOBILE BANKING TEHADAP KEPUASAN NASABAH PT. BANK RAKYAT INDONESIA (PERSERO UNIT SANGAJI MUARA TEWEH) - Sofia SOFIA; Devi Febri Yanti (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2025)
Thisistudyiaimsitoianalyzeithe effect of representativeness and digital marketing on customer satisfaction with information transformation as aimediatingivariable at PT Bank Rakyat Indonesia (Persero) Unit Sangaji Muara Teweh. This research employed aiquantitativeiapproachiwithianiexplanatoryiresearch designiandisurveyimethod. Data were collected using a Likert-scale questionnaire from 90 respondents who had actively used the BRImo application for at least the last three months. Dataianalysisiwasiconductediusing multiple linear regression and path analysis with SPSS 25. The results show that representativenessihasinoidirectieffect on customer satisfaction when mediated by information transformation, whereas digital marketing has a positive and significant effect both directly and indirectly through information transformation. Information transformation was found to have the most dominant effect on customer satisfaction, indicating that optimizing digital systems is a key factor in enhancing service experience. This study concludes that strengthening information transformation and implementing data-driven digital marketing strategies are crucial to sustainably improving customer satisfaction.